Development of Anthraquinone Derivatives as Ectonucleoside Triphosphate Diphosphohydrolase (NTPDase) Inhibitors With Selectivity for NTPDase2 and NTPDase3 - Younis Baqi; Mahmoud Rashed; Laura Schäkel; Enas M. Malik; Julie Pelletier; Jean Sévigny; Jean Sévigny; Amelie Fiene; Christa E. Müller (Frontiers Media S.A., 2020)
Ectonucleoside triphosphate diphosphohydrolases (NTPDases) catalyze the hydrolysis of nucleoside tri- and di-phosphates to mono-phosphates. The products are subsequently hydrolyzed by ecto-5'-nucleotidase (ecto-5'-NT) to nucleosides. NTPDase inhibitors have potential as novel drugs, e.g., for the treatment of inflammation, neurodegenerative diseases, and cancer. In this context, a series of anthraquinone derivatives structurally related to the anthraquinone dye reactive blue-2 (RB-2) was synthesized and evaluated as inhibitors of human NTPDases utilizing a malachite green assay. We identified several potent and selective inhibitors of human NTPDase2 and -3. Among the most potent NTPDase2 inhibitors were 1-amino-4-(9-phenanthrylamino)-9,10-dioxo-9,10-dihydroanthracene-2-sulfonate (20, PSB-16131, IC50 of 539 nM) and 1-amino-4-(3-chloro-4-phenylsulfanyl)phenylamino-9,10-dioxo-9,10-dihydroanthracene-2-sulfonate (48, PSB-2020, IC50 of 551 nM). The most potent NTPDase3 inhibitors were 1-amino-4-[3-(4,6-dichlorotriazin-2-ylamino)-4-sulfophenylamino]-9,10-dioxo-9,10-dihydroanthracene-2-sulfonate (42, PSB-1011, IC50 of 390 nM) and 1-amino-4-(3-carboxy-4-hydroxyphenylamino)-9,10-dioxo-9,10-dihydroanthracene-2-sulfonate (33, PSB-2046, IC50 of 723 nM). The best NTPDase2 inhibitor 20 showed a non-competitive inhibition type, while the NTPDase3 inhibitor 42 behaved as a mixed-type inhibitor. These potent compounds were found to be selective vs. other NTPDases. They will be useful tools for studying the roles of NTPDase2 and -3 in physiology and under pathological conditions.